The stellar photosphere–hydrogen ionization front interaction in classical pulsators: a theoretical explanation for observed period–colour relations. Issue 1 (22nd January 2020) - Das, Susmita; Kanbur, Shashi M; Bellinger, Earl P; Bhardwaj, Anupam; Singh, Harinder P; Meerdink, Brett; Proietti, Nicholas; Chalmers, Anthony; Jordan, Ryan
ABSTRACT: Period–colour and amplitude–colour (PCAC) relations can be used to probe both the hydrodynamics of outer envelope structure and evolutionary status of Cepheids and RR Lyraes. In this work, we incorporate the PCAC relations for RR Lyraes, BL Her, W Vir, and classical Cepheids in a single unifying theory that involves the interaction of the hydrogen ionization front (HIF) and stellar photosphere and the theory of stellar evolution. PC relations for RR Lyraes and classical Cepheids using the Optical Gravitational Lensing Experiment (OGLE-IV) data are found to be consistent with this theory: RR Lyraes have shallow/sloped relations at minimum/maximum light, whilst long-period ( P > 10 d) Cepheids exhibit sloped/flat PC relations at minimum/maximum light. The differences in the PC relations for Cepheids and RR Lyraes can be explained based on the relative location of the HIF and stellar photosphere which changes depending on their position on the Hertzsprung–Russell diagram. We also extend our analysis of PCAC relations for type II Cepheids in the Galactic bulge, Large and Small Magellanic Clouds using OGLE-IV data. We find that BL Her stars have sloped PC relations at maximum and minimum light similar to short-period ( P < 10 d) classical Cepheids. W Vir stars exhibit sloped/flat PC relation at minimum/maximum light similar to long-period classical Cepheids. We also compute state-of-the-art 1D radiation hydrodynamic models of RR Lyraes, BL Her and classical Cepheids using the radial stellar pulsation code in mesa to further test these ideas theoretically and find that the models are generally consistent with this picture. We are thus able to explain PC relations at maximum and minimum light across a broad spectrum of variable star types.